Gambaran Kasus Paramphistomiasis Pada Sapi Bali (Bos sondaicus) Berdasarkan Data Hasil Pemeriksaan Post Mortem Pada Hewan Kurban - Purwono, Edi; Mubarokah, Wida Wahidah; Makmun, Lutfan; Akbarrizki, Muzizat (Universitas Muhammadiyah Kotabumi, 2025)
Paramphistomiasis is one of the important parasitic diseases that affect ruminant animals. This disease is caused by infection with flatworms (trematodes) of the genus Paramphistomum. These worms can cause disturbances in the digestive tract of livestock, which can ultimately reduce the productivity of the livestock being raised and even lead to the death of the animals. The objective of this study was to determine the prevalence of Paramphistomiasis in cattle slaughtered during the Idul Adha holiday in Manokwari Regency, West Papua Province, through post-mortem examination or examination conducted after the slaughtering process was completed. This study is a survey study. The study population consists of cattle slaughtered during the Idul Adha holiday in Manokwari Regency, West Papua Province. Sampling was conducted using non-probability sampling techniques, with 202 samples collected using purposive sampling methods. The results of the study indicate that 71 samples out of the total number of sacrificial animals slaughtered during Eid al-Adha tested positive for infection with Paramphistomum sp, with a prevalence rate of 35%, as evidenced by the detection of Paramphistomum sp worms following slaughter and rumen organ dissection. Based on the results and discussion, it can be concluded that the incidence of paramphistomiasis in Manokwari Regency is relatively high. This is likely due to inadequate management practices and the continued use of a semi-intensive management system.